Incorporation of Professionalism Expectations and Evaluative Processes Within a College of Pharmacy - Schwartz, Amy (Am J Pharm Educ, 2018)
Objective. To determine professionalism factors of interest to the University of South Florida (USF) College of Pharmacy (COP) and develop a programmatic plan to monitor the professionalization of students, faculty, preceptors and staff. Methods. In 2013, the USF COP began investigating how best to incorporate processes to capture professionalism across all aspects of the program. A Professionalism Task Force was convened to identify key professionalism factors valued by faculty and preceptors to be incorporated in pharmacy practice experiences, didactic courses, faculty, and preceptor performance evaluations. A factor analysis was performed to identify items for inclusion in professional practice experience evaluations, course syllabi, faculty, preceptor and staff evaluations. Results. The analysis identified 11 factors for practice experiences, three for syllabi, and five for performance evaluations. The information from the factor analysis spurred additional discussion that led to the development of a programmatic plan for professionalization. Conclusion. A brief description of the programmatic professionalization plan is provided, including possible assessment processes. The goal of this endeavor was to ensure appropriate support and development of professionalization across the COP community.